2022
DOI: 10.1039/d2ra00668e
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing interfacial characteristics of the CS contact with MX2 (M = Mo, W; X = S, Se, Te) and MXY ((X ≠ Y) = S, Se, Te) monolayers

Abstract: Electronic band structure, type of Schottky contact and Schottky barrier height established at the interface of the CS–MX2 (M = Mo, W; X = S, Se, Te) and CS–MXY ((X ≠ Y) = S, Se, Te) MS vdWH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…41 The planar, buckling and puckered structures are three different possible geometrical configurations for each of these 2D binary monolayers. 42 The favoured hybridization in group V monolayers (arsenene and phosphorene) is sp 3 , but the hexagonal planar structure favours sp 2 , showing that the hybridization in group IV-VI binary monolayers is comparable to that of arsenene and phosphorene. 42 Due to the intense overlap of the conduction and valence bands, it has been found that CS monolayers in the planar configuration are metallic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The planar, buckling and puckered structures are three different possible geometrical configurations for each of these 2D binary monolayers. 42 The favoured hybridization in group V monolayers (arsenene and phosphorene) is sp 3 , but the hexagonal planar structure favours sp 2 , showing that the hybridization in group IV-VI binary monolayers is comparable to that of arsenene and phosphorene. 42 Due to the intense overlap of the conduction and valence bands, it has been found that CS monolayers in the planar configuration are metallic.…”
Section: Introductionmentioning
confidence: 99%
“…42 The favoured hybridization in group V monolayers (arsenene and phosphorene) is sp 3 , but the hexagonal planar structure favours sp 2 , showing that the hybridization in group IV-VI binary monolayers is comparable to that of arsenene and phosphorene. 42 Due to the intense overlap of the conduction and valence bands, it has been found that CS monolayers in the planar configuration are metallic. 40 Inspired by these, carbon sulphide (CS) was predicted to show high efficient photocatalysts for water splitting with high carrier mobility (3.23 × 10 4 cm 2 V −1 s −1 ) and moderate band gap (2.41 eV), comparable to those of other newly reported 2D photocatalysts.…”
Section: Introductionmentioning
confidence: 99%